Deliberation and Development: Rethinking the Role of Voice and Collect ive Action in Unequal Societies - Heller, Patrick; Rao, Vijayendra (World Bank Publications, 2015)
This book marries two fields that rarely converse with one another:del iberative democracy and development studies. The study ofdeliberation— which explores normative and practical questions aroundgroup-based dec ision making through discussion or debate—has emergedas a critical are a of study over the past two decades. Concurrently, the fieldof develo pment has seen a spurt of interest in community-led developmentand par ticipation premised on the ability of groups to arrive at decisionsand manage resources via a process of discussion and debate. Despite theg rowing interest in both fields, they have rarely engaged with one anot her.This book, which brings together new essays by some of the leading scholarsin the field, deepens our understanding of participatory deci sion makingin developing countries while initiating a new field of stu dy for scholarsof deliberation. In the process, it sheds light on how to best design andimplement policies to strengthen the role of partici pation in development.